Ideación Suicida en Estudiantes de 15 a 18 años de la Institución Educativa Técnica La Sagrada Familia de Ibagué - Cruz Gordillo, Jessica Alexandra (Psicología, 2018)
The present investigation is oriented towards the quantitative analysis on the suicide risk factor that is evident in the student population of the Sacred Family educational institution in the city of Ibague, with a sample of 141 students between 15 and 18 years of age, this was carried out under a non-experimental and descriptive study, considering the data collection through Beck's Scale of Hopelessness (1974). Regarding the results, suicidal ideation tendency was found in 3 adolescents of 17 years old, students of 11th grade, in the same way there is no evidence of an incidence in social factors that determine a predisposition to such problem